Twenty years after Gilmore: Who is being executed? - Culver, John H. (American journal of criminal justice, 1999)
This research profiles the 432 felons executed between 1977, the first execution in the post-Gregg era, and 1997. The 432 death row inmates executed during this period were males (with one exception), convicted of murder under at least one aggravating circumstance, and had extensive criminal histories. Most held low-prestige jobs prior to their last arrest, achieved less than a high school education, and had serious mental or emotional problems. Only a handful of these executions generated any publicity. Those who were executed were lower class individuals unlikely to arouse any public sympathy.